ANALYSIS OF VISUAL ELEMENTS AND DESIGN HIERARCHY ON THE MOVIE POSTER HOME SWEET LOAN (2024) IN PERSPECTIVE VISUAL COMMUNICATION DESIGN - Badar Ahmad Sidiq; Muhammad Ilham Mulyadin; Muhammad Zidane Al Fakhri; Aliyah (Journal Informatic, Education and Management (JIEM), 2026)
A film poster is not just a promotional tool , it also serves as a narrative representation of the entire cinematic work offered to the public . This study aims to analyze the visual elements and design hierarchy in the poster for the film Home Sweet Loan (2024) by director Sabrina Rochelle Kalangie, produced by Visinema Pictures and Legacy Pictures. This study uses a qualitative approach with semiotic analysis and visual communication design analysis methods , starting from the theoretical framework of visual composition , typography , color , and the hierarchy of graphic elements . The results of the analysis show that the poster applies a systematic visual hierarchy through typographic arrangements , lighting contrasts , and the placement of figures that reflect the social dynamics and family relationships in the film's narrative . The dominant earth tone color palette , the composition of the dining table as a visual focus , and the contrasting expressions of the main character compared to other characters are effective communication strategies to convey the theme of financial struggles and family problems . Overall , the Home Sweet Loan poster successfully encapsulates the emotional complexity of the film into a consistent and communicative visual frame . , while also showing the maturity of visual communication design practices in contemporary Indonesian films .